The M3 Phosphorylation Site Is Required for Trafficking and Biological Roles of PIN-FORMED1, 2, and 7 in Arabidopsis - Ki, Daeeun; Sasayama, Daisuke; Cho, Hyung-Taeg (Frontiers in Plant Science, 2016)
Asymmetrically localized PIN-FORMED (PIN) auxin efflux carriers play key roles in regulating directional intercellular auxin movement, generating local auxin gradients, and diverse auxin-mediated growth and development. The polar localization of PINs is controlled by phosphorylation in the central hydrophilic loop (HL) of PINs. Although the M3 phosphorylation site, including phosphorylatable 5 Ser/Thr residues, is conserved among long HL-PINs, its native role has only been characterized in PIN3. In this study, we examined the role of M3 phosphorylation site of PIN1, PIN2, and PIN7 in intracellular trafficking, phosphorylation, and biological functions of those PINs in their native expressing tissues. Phosphorylation-defective mutations of the phosphorylatable residues in the M3 site of PIN1-HL led to alteration in subcellular polarity of PIN1 and caused defects in PIN1-mediated biological functions such as cotyledon development, phyllotaxy of vegetative leaves, and development of reproductive organs. The M3 mutations of PIN7 interfered with its polar recycling in the root columella cell in response to gravity stimulus and partially disrupted root gravitropism. On the other hand, the M3 site of PIN2 was shown to be necessary for its targeting to the plasma membrane. In vitro phosphorylation assay showed that the M3 phosphorylation residues of PIN1 are the partial targets by PINOID kinase. Our data suggest that the M3 phosphorylation site is functionally conserved among long HL-PINs by playing roles for their subcellular trafficking and auxin-mediated developmental processes.